2020
DOI: 10.4047/jap.2020.12.5.273
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond strengths of aged and non-aged CAD/CAM materials after different surface treatments

Abstract: PURPOSE To assess shear bond strengths (SBS) of resin composites on aged and non-aged prosthetic materials with various surface treatments. MATERIALS AND METHODS Cerasmart (CE), Vita Enamic (VE), Vita Mark II (VM), and IPS e.max CAD (EC) blocks were sliced, and rectangular-shaped specimens (14 × 12 × 1.5 mm; N = 352) were obtained. Half of the specimens were aged (5000 thermal cycles) for each material. Non-aged and aged specimens were divided into 4 groups according to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 36 publications
5
11
0
Order By: Relevance
“…Adhesive failure patterns have been associated with low values of bond strength, cohesive and mixed patterns seem to be considered more acceptable because they suppose a better infiltration of the resinous cementing agent in the conditioned surface of the PICN. 27,28 In the present investigation, the predominant pattern was mixed for the hydrofluoric acid and self-etching ceramic primer groups, consistent with the highest values of bond strength in the study, and an almost exclusive pattern of adhesive failures for the airborne-particle abrasion group, in which the lowest values were obtained.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Adhesive failure patterns have been associated with low values of bond strength, cohesive and mixed patterns seem to be considered more acceptable because they suppose a better infiltration of the resinous cementing agent in the conditioned surface of the PICN. 27,28 In the present investigation, the predominant pattern was mixed for the hydrofluoric acid and self-etching ceramic primer groups, consistent with the highest values of bond strength in the study, and an almost exclusive pattern of adhesive failures for the airborne-particle abrasion group, in which the lowest values were obtained.…”
Section: Discussionsupporting
confidence: 87%
“…Bond strength can be affected by hydrolytic degradation of the materials in the small adhesive area, storage in water for long periods of time, or thermal cycling. 28,29 Conclusions With the limitations of the present investigation, the self-etching ceramic primer and hydrofluoric acid followed by silane were reported to be statistically equal at 20 and 60 seconds. The 20 second time seems to be a more reasonable option than 60 seconds applying these surface treatments on a PICN.…”
Section: Discussionmentioning
confidence: 58%
“…In the present study, HF acid application showed better results considering higher SBS valueseither with conventional silane (13 mpa) or multi-purpose primer (12.6 mpa) and not observed adhesive failure type. This is in line Khaled M Naeim withthe results of Kilinc et al, (2020) (10) who concluded that HF etching was more effective in achieving durable bond strength for glass ceramics. Surface analyses of HF acid-and APF gel-etched porcelain have revealed the production of markedly different etching patterns.…”
Section: Discussionsupporting
confidence: 86%
“…It produced only a few shallow pores and undercuts, whereas etching with HF acid showed greater roughness and irregularity. (8,10) This can be the reason for significantly decreased SBS value measured when APF gel was used only for 4 min with silane treatment (4.6 mpa) in comparison to HF acid with silane group (13 mpa).…”
Section: Discussionmentioning
confidence: 99%
“…In order to calculate the sample size, a previous research performed in 2020 was used as a reference, where it was calculated that 10 specimens per group supplied a power of 0.9. [9] The mean and standard deviation values were calculated for each group in each test. Data were explored for normality using Kolmogorov-Smirnov and Shapiro-Wilk tests, data showed parametric (normal) distribution.…”
Section: Resultsmentioning
confidence: 99%